2021
DOI: 10.1136/bmj.n1537
|View full text |Cite
|
Sign up to set email alerts
|

Associations between statins and adverse events in primary prevention of cardiovascular disease: systematic review with pairwise, network, and dose-response meta-analyses

Abstract: Objective To assess the associations between statins and adverse events in primary prevention of cardiovascular disease and to examine how the associations vary by type and dosage of statins. Design Systematic review and meta-analysis. Data sources Studies were identified from previous systematic reviews and searched in Medline, Embase, and the Cochrane Central Register of Controlled Trials, up to August 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
1
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 123 publications
(198 reference statements)
5
108
1
11
Order By: Relevance
“…This could be due to underreporting of statinassociated pain (by the patients themselves, or under-recording by GPs in the clinical record; 3.4% of participants prescribed simvastatin or atorvastatin received a relevant GP diagnosis (including myalgia, myositis), compared to previous studies with systematic ascertainment of muscle effects that reported up to 25% of patients with muscle symptoms (5,9,43). A recent systematic review of RCTs reported that statins were not associated with clinically confirmed muscle disorders, consistent with our results (patients may report muscle symptoms, but these are not clinically confirmed) (44). Additionally, our ability to analyse dose was limited due to data availability, and SLCO1B1*5 has been linked to muscular complaints (and atorvastatin intolerance) especially in patients receiving high doses of atorvastatin (45).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This could be due to underreporting of statinassociated pain (by the patients themselves, or under-recording by GPs in the clinical record; 3.4% of participants prescribed simvastatin or atorvastatin received a relevant GP diagnosis (including myalgia, myositis), compared to previous studies with systematic ascertainment of muscle effects that reported up to 25% of patients with muscle symptoms (5,9,43). A recent systematic review of RCTs reported that statins were not associated with clinically confirmed muscle disorders, consistent with our results (patients may report muscle symptoms, but these are not clinically confirmed) (44). Additionally, our ability to analyse dose was limited due to data availability, and SLCO1B1*5 has been linked to muscular complaints (and atorvastatin intolerance) especially in patients receiving high doses of atorvastatin (45).…”
Section: Discussionsupporting
confidence: 87%
“…Trials are showing that genotype-guided treatment for antiplatelet therapy reduces adverse events (48). Though a recent systematic review reported that safety concerns were limited in statin therapy (44) this was in the general population; in sub-populations carrying the SLCO1B1*5 decreased function variant, especially women, tailoring the specific statin or dose may improve outcomes, and could highlight patients to target with novel agents for cholesterol lowering (49).…”
Section: Discussionmentioning
confidence: 99%
“…One of these agents, the monoclonal antibody against P-selectin inclacumab, has shown some promise in minimizing cardiac damage in patients with acute coronary syndrome undergoing percutaneous coronary intervention [95,96]. The results of our systematic review and meta-analysis suggest that soluble selectin-lowering might also be important in the context of statin therapy, an established treatment option in primary and secondary cardiovascular prevention [97][98][99]. Whist the exact mechanisms of action involved in the statin-mediated reduction in soluble selectin concentrations remain elusive, in vitro studies have shown that atorvastatin significantly prevents the overexpression of E-Selectin induced by cigarette smoking extract in human umbilical vein endothelial cells through inhibiting the NF-K B signal pathway, a critical pathway involved in inflammatory processes [100,101].…”
Section: Discussionmentioning
confidence: 94%
“…Elevations in circulating cholesterol concentrations significantly increase the risk of atherosclerosis and its clinical manifestations, particularly myocardial infarction, ischemic stroke, and peripheral arterial disease [ 1 , 2 ]. Statins, through the inhibition of the enzyme 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase, the rate-limiting step in the mevalonate pathway through which cells synthesize cholesterol, are the most commonly prescribed drugs for the treatment of hypercholesterolaemia and the management of cardiovascular risk worldwide in view of their favourable efficacy and safety profile [ 3 ]. However, while the main action is mediated by lowering the concentrations of specific cholesterol fractions, particularly low-density lipoprotein (LDL) [ 4 ], the atheroprotective effects of statins involve other mechanisms, normally described as pleiotropic effects [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%